Peningkatan Kemampuan Menulis Surat Lamaran Kerja melalui Pendekatan Kontekstual pada Siswa SMK BAZNAS Makassar - Ririn Sabriadi (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to improve the ability to write job application letters among 12th-grade students at SMK BAZNAS Makassar through a contextual approach. The background of this research is based on the students’ low skills in writing job application letters in accordance with linguistic conventions and proper text structure. The method used is Classroom Action Research (CAR) conducted in two cycles. Data collection techniques include observation, writing tests, and documentation. The results of the study show that the contextual approach significantly enhances students' ability to write job application letters, as evidenced by an increase in the average score from 68.5 in the pre-cycle to 81.2 at the end of the second cycle. This research recommends that Indonesian language teachers at vocational schools implement contextual approaches as an effective and relevant teaching strategy aligned with workplace demands.